Reinterpretation of Water Temperature Measurements - Aulia Galama-Tirtamarina; Mirjam Blokker (Engineering Proceedings)
Drinking water temperatures above 25 °C have been measured more often since Dutch drinking water companies are required to take Random Day Time (RDT) samples. The objective of this study was to obtain more information from the required temperature measurements. A total of 34,595 drinking water temperature measurements between 2012 and 2021 were analyzed and compared with the temperature prediction from a soil temperature model (STM), developed by Blokker and Pieterse-Quirijns (2013) and Agudelo-Vera et al. (2015). More than 300 exceedances of the modeled urban soil temperature were found (ca. 1%). While there were only four measurements with temperatures higher than 25 °C. By looking at the locations of the temperature exceedances, drinking water companies can further investigate whether there are other heat sources near these locations. Using the STM calculations as a reference for the measured drinking water temperature has provided more options for locating hotspots.